2003
DOI: 10.1086/368239
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of Early F Stars: γ Doradus Candidates and Possible Metallic Shell Stars

Abstract: We obtained high-resolution spectroscopic observations of 34 Doradus candidates. From the redwavelength spectra, we determined spectral classes, radial velocities, and projected rotational velocities. The spectra of seven late A or early F stars show metallic lines that have composite profiles consisting of a narrow component near the center of a broad line, indicating that they may be shell stars or binaries. Several stars, including HD 152896, HD 173977, HD 175337, and HD 195068/9, show large line profile as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 74 publications
8
51
1
Order By: Relevance
“…The frequency given by Koen & Eyer (2002) for the Hipparcos data (1.78085 d −1 ) is not present in any of the significant threefrequency solutions. Fekel et al (2003) observed no velocity changes in the 2 spectra they obtained, but Mathias et al (2004) did. The latter also mentioned possible line-profile variations in the blue wing of the lines.…”
Section: Hd 2842 = Hip 2510mentioning
confidence: 81%
“…The frequency given by Koen & Eyer (2002) for the Hipparcos data (1.78085 d −1 ) is not present in any of the significant threefrequency solutions. Fekel et al (2003) observed no velocity changes in the 2 spectra they obtained, but Mathias et al (2004) did. The latter also mentioned possible line-profile variations in the blue wing of the lines.…”
Section: Hd 2842 = Hip 2510mentioning
confidence: 81%
“…The large line asymmetries described by Fekel et al (2003) are certainly due to the presence of the weak lines of the companion, the residual flux of which are about 1/3 that of the main component. We measured the lines of the components using a Gaussian fit to both Ti  and Fe  lines.…”
Section: The Binary Systemmentioning
confidence: 95%
“…The average of the derived velocities are listed in Table 1. We also considered the two velocity values given by Fekel et al (2003) to derive the parameters of the binary orbit that are provided in Table 2. This orbit is represented, for both components, in Fig.…”
Section: The Binary Systemmentioning
confidence: 99%
See 2 more Smart Citations